340 Calcaneal bone density and bone stress injury in NCAA division I athletes and non-intercollegiate athlete college students. (3rd March 2020) - Bennett, Jason; Austin, Tricia; Hayes, Ann; Reinking, Mark
Abstract : Background: There is limited evidence describing the relationship between calcaneal bone mineral density (cBMD) and activity level or lower extremity overuse bone injury (LEOBI). Objective: The purposes of this study were to: 1) compare cBMD of intercollegiate athletes (ICA) and non-intercollegiate athlete (NA) college students, 2) examine the influence of physical activity on cBMD in NA, and 3) determine if there is an association between cBMD and the development of LEOBI. Design: Prospective, cohort study. Setting: NCAA Division I University. Participants: 84 ICA and 103 NA college students. Assessment: ICAs provided injury and menstrual history, were measured for cBMD at the beginning and end of the year, and were followed for occurrence of LEOBI. NA college students provided injury and menstrual history and were measured for cBMD. Main outcome measures: Descriptive statistics, statistical analyses of relationships, logistic regression, and t-tests were used in the statistical analyses. Results: Eight ICAs were diagnosed with a LEOBI over the year. There was no difference in initial cBMD between ICAs with and without LEOBI; right (p=0.05) and left cBMD (p=0.07) were lower in those ICAs with LEOBI at the end of the season. The NAs had significantly lower cBMD and speed of sound (SOS) than the ICAs. There were no significant differences in cBMD and SOS values between the 8 ICAs with LEOBI and the 103 NAs. For the NAs, there was no significant correlation between cBMD and activity, however, age of onset of menstruation and cBMD were found to be significantly correlated (p<0.05). Conclusions: cBMD was significantly lower in NAs as compared to ICAs. The ICAs with LEOBI did not have significantly different cBMD than the NAs. The difference in cBMD between ICAs and NAs may be activity related, but differences in cBMD among the NAs was not related to activity level.